2020
DOI: 10.1186/s13048-020-00726-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of activating GABAB1 receptor on proliferation, migration, invasion and epithelial-mesenchymal transition of ovarian cancer cells

Abstract: Objective This study aimed to explore the effects of activating GABAB1 receptor by baclofen on proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) of ovarian cancer cells. Results One hundred μmol/L, 200 μmol/L and 300 μmol/L were selected as low, medium and high baclofen concentrations respectively. Cells were divided into four groups: Control, 100 μmol/L, 200 μmol/L and 300 μmol/L. Compared with the control group, the viability, colony formation, migration and invasion of SKOV3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…[ 12–14 ] Enhancing the sensitivity of OC cells to DDP is particularly critical in the treatment of OC. [ 15 ] In this study, we observed that LTX‐315 had the effects of inhibiting the cell viability and promoting the apoptosis in OC cells. Furthermore, LTX‐315 remarkably inhibited the drug resistance of OC cells to DDP.…”
Section: Discussionmentioning
confidence: 83%
“…[ 12–14 ] Enhancing the sensitivity of OC cells to DDP is particularly critical in the treatment of OC. [ 15 ] In this study, we observed that LTX‐315 had the effects of inhibiting the cell viability and promoting the apoptosis in OC cells. Furthermore, LTX‐315 remarkably inhibited the drug resistance of OC cells to DDP.…”
Section: Discussionmentioning
confidence: 83%
“…Neurotransmitters can play a key role in the regulation of tumor cells and can influence the formation and development of tumors. Experimental data have shown that γ-aminobutyric acid receptors are widely expressed in a variety of cancer tissues and cancer cells and are related to the progression of ovarian cancer [ 1 , 37 , 38 ]. N-acetyl-aspartic acid is considered as a marker for the diagnosis of complex cystic masses such as benign teratoma, endometriosis, and tubo-ovarian abscesses [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is considered one of the most fatal cancers among malignant tumors [ 1 ]. Difficulties in the early diagnosis of ovarian cancer due to a lack of effective screening strategies lead to high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Our results, presented here indicate that the antagonists of these metabolism-derived ligands can effectively disrupt the autocrine signaling loop and inhibit ovarian cancer cell proliferation ( Figure 7 , Figure 8 , Figure 9 , Figure 10 and Figure 11 ). In this context, it should be noted here that baclofen, a selective agonist for GABA B receptor [ 83 ], has been shown to inhibit cell proliferation in SKOV3 cells [ 84 ], a cell line that represent clear cell carcinoma of the ovary [ 51 ]. Contrary to this observation, our studies indicate that the GABA B -antagonist inhibit cell proliferation in multiple ovarian cancer cell lines representing HGSOC ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%